Covert game - Feehan, Christine (Feehan, Christine. GhostWalker novel., 2018)
"Treason, torture and temptation haunt the GhostWalkers in their most dangerous adventure yet, as Christine Feehan's #1 New York Times bestselling series hits an explosive new high. Rescuing an industrial spy from the hands of a criminal mastermind is a suicide mission for the GhostWalkers. And there's no one more up to the task than Gino Mazza. He's the perfect killing machine--a man driven by demons so dark and destructive that his blighted soul has given up trying to find solace. But his laser-sharp focus on his target has transformed into something nearing desire. A treasonous senator dangled top secret GhostWalker data in front of a Chinese crime lord, and he bit. Zara Hightower, one of the world's leading experts on artificial intelligence, was sent in to psychically wipe the crime lord's computer network. She succeeded, but at a huge cost. Now she's the captive of a man who has descended into paranoid madness. Torture and death await her... But GhostWalkers never leave one of their own in enemy territory. And it's up to Gino to save Zara, or kill her if it turns out she's led them into a trap. Either way, heaven or hell won't stop him.."--